Neighbourhoods in Transition. Brownfield Regeneration in European Metropolitan Areas. - (:unkn) unknown (Springer, 2022)
Neighbourhoods in Transition begins with an overview of historic urban development and strategic areas in the hearts of towns to be developed. It then defines several key issues related to the topic, including urban brownfields, regeneration projects, and sustainability issues related to neighbourhood development. The second part of this book is focused on support tools, explaining the challenges faced, the steps involved in a regeneration process, and offering an operational monitoring tool. It applies the unique tool to case studies in three selected neighbourhoods and the outcomes of one case study are also presented and discussed, highlighting its benefits.
Keywords: Metropolregion; Stadterneuerung; Brachflächenrecycling; Entwicklungspotenzial; Entwicklungsprojekt; Projektsteuerung; Nachhaltige Stadtentwicklung; Stadtquartier; Quartiersentwicklung; Bauen im Bestand; Industriebrache; Stadtreparatur; Nachhaltige Entwicklung; Monitoring; Evaluation; Fallbeispiel